Prevalence and correlates of soil-transmitted helminths in schoolchildren aged 5 to 18 years in low- and middle-income countries: a systematic review and meta-analysis - Agrawal, Ritik; Pattnaik, Sweta; Kshatri, Jaya Singh; Kanungo, Srikanta; Mandal, Nityananda; Palo, Subrata Kumar; Pati, Sanghamitra (Frontiers in Public Health, 2024)
Background: According to Global Burden of Disease (GBD) 2019 report, the disability adjusted life years (DALYs) lost due to soil transmitted helminths (STHs) were as high as 1.5 million and 5.9 million are at risk of acquiring STH. The regions with the highest prevalence of STH infections include Sub-Saharan Africa, China, South America, and Asia. While numerous fragmented studies on STH have do exist, however, comprehensive information on prevalence, geographic distribution of different species, as well as their regional variations is limited in context of STHs. Present systematic review and meta-analysis study attempts to provide a summary of prevalence, geographical variation, and determinants of STHs among school going children aged 5 to 18 years.Methods: An extensive literature search was carried out through PubMed, Embase, Cinhal and Psychinfo for studies published between 1999 to 2022 reporting the rate of STH infection among school going children aged 5-18 years. Random-effects model was employed in this meta-analysis due to anticipated heterogeneity. Subgroup analysis was carried out based on gender and STH species because of expected geographical variation.Results: A total of 19,725 of the 49,630 children examined, were infected with STH yielding an overall pooled prevalence of 37.16% (95% CI: 29.74 -44.89). The prevalence was highest in Western Pacific 50.41% (95% CI: 33.74 -67.04) followed by Europe 39.74% (95% CI: 20.40 -61.0) and Africa 37.10% (95% CI: 26.84 -47.95). Ascaris lumbricoides was found to be the most prevalent helminth having prevalence of 24.07% (95% CI: 17.07 -31.83) Conclusions: Western Pacific region is classified as High-risk Zone (HRZs) whereas, South East Asia, Africa, Europe and Eastern Mediterranean regions are classified as moderate risk zones (MRZs). We found a reduction in pooled prevalence of STH infection by 12% during 1999 to 2012. Ascaris lumbricoides was the predominant species among school going children. 5 Mass Drug Administration (MDA) of Albendazole tablets and improved water and sanitation hygiene (WASH) practices are effective for controlling and preventing STH. Ensuring their implementation and access is crucial in addressing the problem.